Thermal Energy Storage Optimization in Shopping Center Buildings - Totok R. Biyanto; Akhmad F. Alhikami; Gunawan Nugroho; Ridho Hantoro; Ridho Bayuaji; Hudiyo Firmanto; Joko Waluyo; Agus Imam Sonhaji (Journal of Engineering and Technological Sciences, 2015)
In this research, cooling system optimization using thermal energy storage (TES) in shopping center buildings was investigated. Cooling systems in commercial buildings account for up to 50% of their total energy consumption. This incurs high electricity costs related to the tariffs determined by the Indonesian government with the price during peak hours up to twice higher than during off-peak hours. Considering the problem, shifting the use of electrical load away from peak hours is desirable. This may be achieved by using a cooling system with TES. In a TES system, a chiller produces cold water to provide the required cooling load and saves it to a storage tank. Heat loss in the storage tank has to be considered because greater heat loss requires additional chiller capacity and investment costs. Optimization of the cooling system was done by minimizing the combination of chiller capacity, cooling load and heat loss using simplex linear programming. The results showed that up to 20% electricity cost savings can be achieved for a standalone shopping center building.